Malaysia Vision Valley 2.0: Potential Impacts on Labu’s Development - Mat Rahim, Nur Izatilrahima; Zaharin , Puteri Mayang Bahjah (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
The study examines the impacts of Malaysia Vision Valley 2.0 (MVV 2.0) on the growth and development of Labu. Leveraging the spatial triad theory and the concept of a sense of place, it explores the relationships between urban spaces and Labu’s economic and social development, emphasising how changes in the built environment influence local livelihoods, social cohesion and identity. The methodology involves archival spatial mapping and interviews with the local community to capture historical trends, community perceptions, and potential challenges. The literature review establishes a theoretical framework highlighting the significance of perceived spaces in shaping urban identities. Findings reveal positive correlations between economic growth and community development, particularly where planned MVV2.0 projects align with existing community needs and capacities. The spatial triad theory guides the interpretation of existing urban spaces, while the concept of a sense of place informs the exploration of Labu's unique identity. Furthermore, the research uncovers challenges related to planning and community engagement, including gaps in coordination between stakeholder and limited opportunities for inclusive participation. This study enriches the discourse on urban development by synthesising theoretical frameworks with empirical data, underscoring MVV 2.0's potential to influence Labu's growth positively, contingent upon carefully considering the city's unique socio-cultural and spatial dimensions. The research recommends for a sustainable approach that balances economic growth with community well-being, preserve Labu’s heritage, and protects the environment, ensuring MVV 2.0 creates a vibrant and resilient community true to Labu’s identity.